Charting the strategic focus for Oricon Sdn Bhd / Mohd. Asri Abdullah ... [et al.] - Abdullah, Mohd. Asri; Razali, Suhardi; Unus, Sazali; Sahat, Affendi; Mohd. Abu Bakar, Badrulzaman (2004)
Sarawak is located on the island of Borneo, and is one of the two states that make up East Malaysia. Both Sarawak and Sabah are separated from Peninsula Malaysia by the South China Sea. With an area of 124,449.51 square kilometres, Sarawak is the largest state in Malaysia, making up some 37.5% of the country's total area. The State is divided into eleven Administrative Divisions. Each Division (or Administration Region) is headed by a Resident and subdivided into between 2 to 4 districts. Kuching is the State capital and the administrative centre for the First Division of Sarawak. It is home to some 458,300 people making it the highest populated city in Sarawak and the 7th highest populated city in Malaysia.